Next century mathematics 10 - Orines Fernando B.; Mercado, Jesus P.; Esparrago, Mirla S.; Manalo, Catalina B.; Reyes, Nestor Jr. V. (Quezon City. Phoenix Publishing House, Inc., 2018)
"This texbook allows mastery of competencies with the hope that the learners will be enabled to better cope with the lessons. Hence, a learner will experience algebra, geometry, and statistics and probability in each grade level. The new edition retains the time-tested features of the original NCM. However, we considered Stephen Covey's strategic step in making our learners understand the mathematical concepts".
Includes glossary.
English text.
Keywords: Mathematics. -- Study and teaching